Electrolyte imbalance and liver function test abnormalities among pregnant women with hyperemesis gravidarum at Wag-himra zone public hospitals, Northeast Ethiopia, 2023: a comparative cross-sectional study - Worede, Abebaw; Deress, Teshiwal; Wondifraw, Habtamu; Fetene, Getnet; Berie, Alemseged (Frontiers in Medicine, 2024)
BackgroundHyperemesis gravidarum affects about 4.8% of pregnant women. It can lead to electrolyte imbalances and liver function disturbances, which may result in pregnancy complications. Despite its prevalence, data on these abnormalities in the study area is scarce. Therefore, the current study investigated these health concerns among HG-affected pregnant women in this region from June to October 2023.MethodA comparative cross-sectional study was conducted on 123 study participants. Socio-demographic, clinical, and anthropometric data were collected using structured questionnaires. Blood samples were taken to determine liver function tests and electrolyte levels. Statistical analysis was performed using a one-way ANOVA with a Tuckey post hoc test, Kruskal-Wallis with a Mann–Whitney U test, and binary logistic regression analysis. A p-value of <0.05 with 95% confidence intervals was considered statistically significant.ResultsThe results showed that pregnant women with hyperemesis gravidarum had significantly higher levels of AST and ALT and lower levels of Na+ and K+ compared to normal pregnant women and non-pregnant women. The abnormalities observed were elevated AST (48.8%), ALT (46.3%), and decreased Na+ (51.2%) and K+ (41.5%). Hyperemesis gravidarum was associated with both electrolyte imbalances and liver function test abnormalities.ConclusionPregnant women with hyperemesis gravidarum experience electrolyte imbalances and liver function test abnormalities. Given the marked increase in liver enzymes and decrease in electrolyte levels, the authors recommend routine laboratory testing of liver function and electrolyte parameters for pregnant women with hyperemesis gravidarum is recommended.